2015
DOI: 10.1111/ics.12259
|View full text |Cite
|
Sign up to set email alerts
|

Mercury(II) determination in commercial cosmetics and local Thai traditional medicines by flow injection spectrophotometry

Abstract: Enhancement of sensitivity and rapidity for Hg(II) assay by FIA could be achieved by adding SDS in ascorbic acid. The method would be useful for routine analysis of Hg(II) in real samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Following water samples, the most frequently analyzed material for mercury was seafood samples, such as fish, shrimp, and seaweed. A few studies reported the determination of mercury in various environmental samples, such as petroleum hydrocarbons [ 88 ], human hair [ 89 , 90 ], phosphate fertilizers [ 53 ], glycerin [ 91 ], sediments [ 55 , 92 , 93 ], cosmetics [ 94 ], living cells [ 66 , 95 ], and tobacco [ 67 ]. However, a few methods [ 74 , 81 , 87 , 96 101 ] did not report their applicability to natural samples.…”
Section: Discussionmentioning
confidence: 99%
“…Following water samples, the most frequently analyzed material for mercury was seafood samples, such as fish, shrimp, and seaweed. A few studies reported the determination of mercury in various environmental samples, such as petroleum hydrocarbons [ 88 ], human hair [ 89 , 90 ], phosphate fertilizers [ 53 ], glycerin [ 91 ], sediments [ 55 , 92 , 93 ], cosmetics [ 94 ], living cells [ 66 , 95 ], and tobacco [ 67 ]. However, a few methods [ 74 , 81 , 87 , 96 101 ] did not report their applicability to natural samples.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic reactions, skin irritation, or neurotoxic problems [54] ELISA, AAS, AFS, CE, CV-AAS, FAAS, FIA, ICP AES, ICP-MS, PVG ICP-MS, HPLC-ICP MS, MP AES, Electrochemical sensors [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Abbreviation: Sweeping-MEKC-sweeping-micellar electrokinetic chromatography; GFAAS-Graphite Furnace Absorption Spectrometry; AAS-Atomic Absorption Spectrometry; LIBS-Laser-Induced Breakdown Spectroscopy; GC-Gas chromatography; HPLC-FLD-High-…”
Section: Whitening Agent Preservativementioning
confidence: 99%
“…Flow injection (FI) spectrophotometry was also developed for the determination of mercury in the cosmetic sample due to its simple, fast, and inexpensive nature compared to other methods such as ICP-MS and UPLC [65,115,116]. Prasertboonyai et al [65] analyzed acne and face-whitening creams using FI spectrophotometry.…”
Section: Mercury Compoundmentioning
confidence: 99%
“…The conventional analytical methods for the detection of Hg 2+ usually rely on the use of advanced instruments based on spectrometric and chromatographic techniques, such as atomic absorption spectrometry (AAS) [ 1 , 5 ], inductively coupled plasma mass spectrometry (ICPMS) [ 6 ], graphite furnace atomic absorption spectrometry (GFAAS) [ 2 ], inductively coupled plasma atomic emission spectrometry (ICP-AES) [ 7 ] and liquid chromatography inductively coupled plasma mass spectrometry (LC-ICP-MS) [ 8 ]. While such approaches have been proven to be highly accurate and sensitive, the complex, expensive and time-consuming procedures associated with these methods call for a simpler alternative for daily analysis and on-site detection in a large number of samples in the field.…”
Section: Introductionmentioning
confidence: 99%